Climate change and agricultural water management in developing countries - Chu, Thai Hoanh, 1949-; Johnston, Robyn; Smakhtin, Vladimir (CABI climate change series, 2015)
This book provides experiences from studies on agricultural water management under climate change as references for agriculture and irrigation planners, decision makers, researchers and students. Chapters 2 and 3 provide an overview of global assessment of climate change impacts and water requirement for future agriculture. Chapters 4-7 provide analyses of crop water requirements in four case studies in developing countries. Chapters 8 and 9 are studies of irrigation management under sea-level rise in Vietnam's Mekong Delta. Chapters 10-12 discuss examples of adaptation alternatives such as water-saving techniques and groundwater exploitation, and related policy settings. The last chapter links the dominant approach of uncertainty presented in the climate change discourse with policy discussions on climate adaptation strategies.